PENGARUH KOMPOS GULMA PAKIS DAN TSP TERHADAP PERTUMBUHAN DAN HASIL TERUNG (Solanum melongena L.) PADA MEDIA GAMBUT - Randi Agustian; Raisa Baharuddin (UIR Press, 2023)
The purpose of this study was to determine the interaction effect and the main effect of fern weed compost and TSP on the growth and yield of eggplant. This research was conducted at the Experimental Garden of the Faculty of Agriculture, Riau Islamic University, Pekanbaru. This research was conducted from January to May 2022. This study used a factorial, completely randomized design (CRD). The first factor is fern weed compost, consisting of 4 levels: 0, 125, 250, and 375 g/polybag. The second factor is TSP, consisting of 4 levels: 0, 3.75; 7.5; and 11.25 g/plant. The treatment was repeated three times. Parameters observed were plant height, number of leaves, number of fruits per plant, fruit weight per plant, weight per fruit, and fruit length. The results showed that there was a significant interaction between fern weed compost and TSP on peat media on the parameters of the number of leaves and weight per fruit, with the best treatment being fern weed compost (375 g/polybag) and TSP fertilizer (7.5 g/plant). The fern weed compost on peat media significantly affected plant height, number of fruits per plant, fruit weight per plant, weight per fruit, and fruit length. The fern weed compost at 375 g/polybag gave the best eggplant growth and yield. TSP fertilizer on peat media was significantly affected by all parameters. Doses of TSP (7.5 g/polybag) gave optimal eggplant growth and yield.